Optimalisasi Penghimpunan Dana Wakaf Melalui E-Payment - Angga Syahputra; Khalish Khairina (Jurnal Ilmiah Ekonomi Islam, 2021)
Waqf is a philanthropy with the highest position in Islam. Apart from being of worship value, waqf is also related to legal, social and economic aspects. The times demand waqf not only in the form of immovable objects such as land and buildings, but also in the form of money. Cash waqf in its development can have a wider impact that can be felt by the community. To optimize the collection of waqf funds, the role of e-payment as a resulting technological innovation needs to be studied more deeply. This study uses a qualitative research type with a literature study model in answering these problems. Data is obtained from various reading sources such as books, previous studies, journals and trusted websites. This research shows that e-payment is proven to help optimize the collection of waqf funds. E-payment can facilitate wāqif in waqf both in terms of mobilization and the amount of funds to be donated. In addition, e-payments are proven to be safer, more convenient and efficient.